Trends in Tramadol: Pharmacology, Metabolism, and Misuse. Issue 4 (August 2017) - Miotto, K.; Cho, A. K.; Khalil, M. A.; Blanco, K.; Sasaki, J. D.; Rawson, R.
Abstract : (Abstracted from Anesth Analg, 124(1):44–51, 2017) The purpose of this review was to examine the literature published over the period January 1980 to January 2016 regarding the use of tramadol for treatment of moderate to moderately severe chronic pain. Tramadol is a synthetic opioid medication with monoaminergic actions and a mechanism similar to serotonin-norepinephrine reuptake inhibitors.